PENGELOLAAN METROPOLITAN SHANGHAI: SUATU AMANAH RAKYAT - Muchtar Ahmad (JIP ( Jurnal Industri dan Perkotaan ), 2005)
High growth of Shanghai Metropolitan in term of economy, and dynamic change toits culture, development and investment policies, and environmental management wereobserved. Population, development fund, and higher education were linkage to thedevelopment. The idea of Shanghai metropolitan development came from top leader in 1992,which has been changed all aspect of life in the city, such as open market economy based onthe experienced of Southeast Asian countries, especially refer to the city and industrialdevelopment. Investment, infrastructure, and public facilities development almost followpopulation growth and environment remedial, so that social issues did not emerged frontallyand the development can be sustained. Fund for infrastructures and public facilities areinnovative collected by means of city administration reform, obligation issued as well asbureaucracy reengineering toward entrepreneurship in city development activities, so thatbudget no supporting from central government necessary.